Efek Antimikroba dari Kapang Endofit Ranting Tanaman Biduri - Kumala, Shirly (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X)
ABSTRACT:Didymella bryniae strain MA71 endophytic fungus was isolatedfrom twigs of Biduri plant (Calotropis gigantea L.Dryand). It has anti yeastactivity and anti bacterial activity against gram positive and negative bacteria.Secondary metabolites were isolated via fermentation process using PDYmedia for 12 hr. Anti microbial activity of these fermentation product was assessedvia agar diffusion method using disk paper. Test result demonstratedthat extracellular secondary metabolites which was extracted using EtOAcwere active towards Staphylococcus aureus ATCC 25923, Escherichia coliATCC 25922 and Bacillus subtilis ATCC 6633. On the other hand, these EtOACextracted metabolites were also active against Candida albicans ATCC 10231.Its inhibitory zone were 17.3 mm, 17.2 mm, 17.41 mm and 11.6 mm respectively.Chloramphenicol was used as positive control for bacteria and nystatinfor yeast. Overall, the se condary metabolites produced by fermentation of endophyticfungi Didymella bryniae strain MA71 have broad spectrum of antibacterial and yeast activity.Keywords: endophytic Fungus, shaked fermentation, secondary metabolites,antimicrobials, and Calotropis gigantea L. Dryand